Cannabidiol as a potential novel treatment for endometriosis by its anti-inflammatory and anti-oxidative effects in an experimental rat model - Ökten, Sabri Berkem; Çetin, Çağlar; Tok, Olgu Enis; Güler, E. M.; İşlek, Sevde; Özcan, Pınar; Fıçıcıoğlu, Cem (Oxford University Press, 2022)
[Abstract Not Available]
Keywords: Experimental Rat Model; Anti-Oxidative Effects; Endometriosis; Anti-inflammatory